Prepration and characterization of Cu-. Fe-, Ag-, Zn- and Ni-doped gelatin nanofibers for possible appliactions in antibacterial nanomedicine - Nuge, Tamrin; Tshai, Kim Yeow; Lim, Siew Shee; Nordin, Norshariza; Hoque, Md. Enamul (Taylor's University, 2017)
A facile and efficient approach to prepare metal nanoparticles doped electrospun gelatin from metal salts precursors was successfully developed. The incorporation of metal ions with antimicrobial activity into electrospun gelatin (Ge-espun) is an attractive approach to control the inflammatory reaction and prevent infection in wound. In this study, metal salts precursors AgNO 3 , Fe(NO 3) 3 .9H 2 O, Cu(NO 3) 2 .3H 2 O, Zn(NO 3) 2 .6H 2 O and Ni(NO 3) 2 .6H 2 O were reduced to metal nanoparticles with acetic acid as solvent and reducing agent. The agglomeration of nanoparticles was inhibited by the gelatin polymer matrix. Electrospinning of both neat Ge-espun and metal-nanoparticles/Ge-espun resulted in the formation of smooth fibres with average diameters of ~280nm and ~40nm-150nm, respectively. The efficacy of metal nanoparticles/Ge-espun against bacteria commonly found on wounds was tested with different metal loading by measuring the inhibition of colony forming units. The results indicated a broad spectrum of antibacterial activity showed by Ag/Ge-espun, followed by Fe/Ge-espun and Zn/Ge-espun. An interesting finding on the efficacy of Cu/Ge-espun and Fe/Ge-espun against the Gram's positive bacteria is worth exploring to further investigate the potential application of metal-based antibiotics against the antibiotic-resistant bacterial strains.